2018
DOI: 10.1111/trf.14640
|View full text |Cite
|
Sign up to set email alerts
|

Age of transfused blood in critically ill adult trauma patients: a prespecified nested analysis of the Age of Blood Evaluation randomized trial

Abstract: In critically ill trauma patients, transfusion of fresh blood did not decrease 90-day mortality or secondary outcomes, a finding similar to the overall population of the ABLE trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…13 Randomized clinical trials published since 2013 revealed similar conclusions. 18,19,[21][22][23] Nevertheless, the Age of Blood Evaluation (ABLE) study 20 suggested a trend toward an increased mortality with fresh RBC units. To our knowledge, no data have been reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Randomized clinical trials published since 2013 revealed similar conclusions. 18,19,[21][22][23] Nevertheless, the Age of Blood Evaluation (ABLE) study 20 suggested a trend toward an increased mortality with fresh RBC units. To our knowledge, no data have been reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Longer storage induces biochemical and morphological modifications of RBC units and accumulation of soluble components that may be deleterious, notably by impairing oxygen delivery to tissues . Consistent with this, some studies suggested that longer RBC storage was associated with worse outcomes in different clinical settings . However, these results have not been consistent, and the benefits of using fresh RBC have been called into question …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, the new metric is superior to ad hoc dichotomous or ordinal categorizations of numbers of RBCs that then serve as predictors in a model for mortality. For example, unlike the recent nested analysis in the Age of Blood Evaluation RCT that showed no difference in 90‐day mortality risk using dichotomous blood age groups (patients receiving fresh blood [no more than 7 days old] vs. patients with standard‐issue blood), analyses involving SBI do not need to be dichotomized; thus, we can use more information about the blood age distribution than these previous authors. Additionally, because it is a scalar, the SBI makes statistical modeling simpler and its interpretation easier, and it has properties that facilitate receiver operating characteristic (ROC) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians would be cautious about extrapolating research findings across different populations or undertaking meta-analysis across different clinical settings 2532. If, as has been hypothesised, red blood cells stored for longer are less effective at improving oxygen transport to tissues, then this may be better tolerated by patients with a greater physiological reserve.…”
Section: Importance Of Case MIXmentioning
confidence: 99%